On The Lagrange Interpolation of Fibonacci Sequence - Muhammad Syifa'ul Mufid; Tahiyatul Asfihani; Lukman Hanafi ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2016)
Fibonacci sequence is one of the most common sequences in mathematics. It was first introduced by Leonardo Pisa in his book Liber Abaci (1202). From the first n + 1 terms of Fibonacci sequence, a polynomial of degree at most n can be constructed using Lagrange interpolation. In this paper, we show that this Fibonacci Lagrange Interpolation Polynomial (FLIP) can be obtained both recursively and implicitly.